Data-Driven Management: Transforming Organizational Decision-Making in the Digital Era - Herikson Tampubolon (Oikonomia : Journal of Management Economics and Accounting, 2026)
The rapid advancement of digital technologies has fundamentally transformed how organizations collect, process, and utilize data to support strategic decision-making. This study examines the transformation of data-driven management within organizations, exploring how the integration of big data analytics, artificial intelligence, and advanced information management systems reshapes organizational decision processes, operational efficiency, and competitive performance. Drawing on a systematic literature review of eighteen recent empirical and theoretical studies (2017–2026), this paper synthesizes key themes including organizational data culture, analytical maturity, technology infrastructure, human capability development, and governance frameworks. Findings indicate that organizations with mature data-driven cultures exhibit significantly higher decision quality, strategic agility, and innovation capacity. However, successful transformation requires overcoming barriers such as data silos, resistance to change, lack of analytical talent, and ethical concerns around data governance. The study proposes a conceptual framework integrating five dimensions of data-driven organizational transformation and recommends a phased implementation pathway for managers seeking to advance their organizations toward full data-driven management.